The Role of Game-Based Learning in Experiential Education: Tool Validation, Motivation Assessment, and Outcomes Evaluation among a Sample of Pharmacy Students - Mariam Dabbous; Anwar Kawtharani; Iqbal Fahs; Zahraa Hallal; Dina Shouman; Marwan Akel; Mohamad Rahal; Fouad Sakr (MDPI AG, 2022)
(1) Background: There is a scarcity of data regarding game-based learning (GBL) in experiential pharmacy education; in addition, the impact of educational games on the attainment of intended learning outcomes and students' motivation to actively learn and practice through non-traditional pedagogical tools are yet to be explored. (2) Methods: This was a prospective quasi-experimental study that introduced GBL into the Pharmacy Practice Experience course of the Bachelor of Pharmacy (BPharm) program at the Lebanese International University in Lebanon. Data collection took place between July and September 2021. The study objectives were to assess the impact of GBL on attaining intended learning outcomes, determine students' motivation to engage in GBL, and assess the impact of this motivation on the attainment of learning outcomes. (3) Results: GBL was associated with a significantly higher exam average (mean difference = 7.152, p < 0.001). Moreover, an active learning motivation assessment scale (ALMAS) was constructed and validated; it was found to have good reliability as well as high sensitivity and specificity, and it determined a good level of motivation to engage in GBL. Game-based learners with higher motivation scores had significantly higher exam averages compared to those with lower scores (Beta = 0.296, 95% CI 0.110-0.545, p = 0.004). (4) Conclusion: GBL was associated with better attainment of intended learning outcomes. Students appear to be motivated to learn by this style of active learning, and motivation is prognostic of the attainment of learning outcomes.